Developing Context Awareness Mobile Application for Blood Donation - Dian Pradhana Sugijarto; Muriati Mukhtar; Nurhizam Safie; Riza Sulaiman (JOIV : International Journal on Informatics Visualization, 2018)
The implementation of context awareness in smartphones is getting broader. Through embedded sensors in smartphones, they are able to detect the device’s location and communicate through radio frequency. By communicating through Near Field Communication (NFC), smartphones are able to read NFC tags in short distances to understand the context of the information. Developing a mobile application in the context of blood donation will allow the application to assist donors through the process of donation and improves the user’s experience. The blood donation study is conducted at the National Blood Centre (NBC) in Malaysia. In developing the mobile application, the system architecture and development pattern were designed. The system architecture is presented to understand the requirements of implementing the application. The Model-View-Presenter (MVP) pattern was utilized to develop the application to ensure the development followed the standard procedure. The mobile application with the context awareness ability was evaluated through interviews with potential end users and the stakeholders of NBC. The evaluation resulted in positives responses and offered valuable feedbacks.